Knowledge, Attitude, Belief And Practice (K.A.B.P) Study On Aids Among Senior Secondary Students - Sharma A.K; Sehgal Virendra N; Kant S; Bhardwaj A (Wolters Kluwer Medknow Publications, 1997)
Research question: What is the level of knowledge , attitude, belief and practices of senior secondary students about AIDS? Objective: To document the knowledge, attitude, belief and practices about AIDS among senior secondary students. Study design: Cross- sectional. Setting: Four senior secondary schools including two boys and two girls schools of Rural Delhi. Participants: Students of senior secondary schools. Study variables: Knowledge, attitude, belief and practices regarding AIDS. Statistical analysis: Proportions. Results: A large majority (83.0%) of students though had heard about AIDS, yet majority of them did not know the possible method of prevention of AIDS. Only 27.1 % girls knew about regular condom usage. Half of them had permissible attitude for pre- marital sex while sexual activity was observed in one- fourth students. Students were less reluctant to discuss about AIDS than sex and teachers were preferred as compared to parents in this regard. Conclusion: School is an ideal setting for adolescents for educating them regarding HIV/AIDS transmission and safer sex behaviour.